If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2y + 6 = 9 Reorder the terms: 6 + 3x + 2y = 9 Solving 6 + 3x + 2y = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + 3x + -6 + 2y = 9 + -6 Reorder the terms: 6 + -6 + 3x + 2y = 9 + -6 Combine like terms: 6 + -6 = 0 0 + 3x + 2y = 9 + -6 3x + 2y = 9 + -6 Combine like terms: 9 + -6 = 3 3x + 2y = 3 Add '-2y' to each side of the equation. 3x + 2y + -2y = 3 + -2y Combine like terms: 2y + -2y = 0 3x + 0 = 3 + -2y 3x = 3 + -2y Divide each side by '3'. x = 1 + -0.6666666667y Simplifying x = 1 + -0.6666666667y
| 7z-7=-42 | | 8n^2+9n-5=5n^2+7n | | 108+8x=111+7 | | 5-7-4n+8n= | | -7(v+4)+2v+7=7v+9 | | 48+4y=-2y | | -4(2n+4)=16 | | f(x)=25+.15x | | Y-13-2x=4 | | 4x-x^2=3x^2-x^3 | | 4(2a+4b)+5(2a+3b)= | | 9k^2-53-6=0 | | F(x)=9+12x | | 2x-3(x+1)=-1 | | 15x+24=16x-72 | | h^2+h-72=0 | | 27x+35=15x+108 | | -2x+10x-125=83 | | 16-9t=47 | | 11x+4=2x-9 | | F(-3)=9+12(-3) | | a+w=250 | | 5b+7=2b+5 | | 13+7x=9x+5 | | 6x+3x-100=80 | | 12x-101-5x-19=6 | | 22x+4=23x+1 | | -2(x-9)+3x=9 | | -2x-9=12 | | 2(y+2)=5(y-1) | | 55x=125 | | 9x+6y=-33 |